Agriculture, food security, nutrition and the Millenium Development Goals - von Braun, Joachim; Swaminathan, Monkombu Sambasivan; Rosegrant, Mark W. (International Food Policy Research Institute, 2004)
..."Today, 1.1 billion people live on less than one US dollar per day (the internationally recognized poverty threshold)—430 million in South Asia, 325 million in Sub-Saharan Africa, 260 million in East Asia and the Pacific, and 55 million in Latin America. Too many children live lives characterized by hunger and illness, and all too often succumb to early death. Moreover, another 1.6 billion people live on between one and two dollars per day, often sliding temporarily below the one dollar per day threshold. To enable all these people to live in dignity, the eight goals to achieve by 2015 are: 1. Eradicate extreme poverty and hunger 2. Achieve universal primary education 3. Promote gender equality and empower women 4. Reduce child mortality 5. Improve maternal health 6. Combat HIV/AIDS, malaria, and other diseases 7. Ensure environmental sustainability 8. Develop a global partnership for development." -- from Text